Industrializing the Earth–Moon system: a conceptual study for a space factory at Lagrange point L5 - Grandl, Werner (Frontiers in Space Technologies, 2025)
The utilization of the natural resources of our Moon and the near-earth asteroids (NEAs) for the benefit of humankind will need industrial plants in space. There are a number of possible locations for the deep-space processing of extracted space-based materials and future industrial activities in cis-lunar space. Prime among these are the Moon itself and the Earth’s five Lagrange points which provide equilibrium between the gravity forces of the Earth and Moon. Especially in Lagrange points L4 and L5, objects remain in stable positions because of the triangle between the object, Earth, and Moon. Building the first space factory in L5, for example, will enable the processing of material and production of goods in zero gravity. Unlike on Earth or the Moon, solar power would be available for 24 h. The industrialisation of cis-lunar space will start with the mining of our Moon. The Lagrange Space Factory (LSF) would start with the processing of lunar material and extract aluminum, iron, titanium, and other materials from lunar regolith. When the metals are extracted from oxides, oxygen is a byproduct. An additional source for material would be the recycling of orbital debris to clean up Earth’s orbit. In the long run, the LSF would also process NEA material, including gold, platinum, and carbon. C-type (carbonaceous) asteroids also contain water ice and organic molecules. The goal would be to produce building material like steel bars and aluminum panels, tubes, and bricks for future space habitats. Oxygen and space-made propellant could also be produced. The isotope helium-3 is abundant on the Moon and can be used for future nuclear fusion in space and on Earth.